Antitumor Activity of Hu14.18-IL2 in Patients With Relapsed/Refractory Neuroblastoma: A Children's Oncology Group (COG) Phase II Study - Shusterman, Suzanne; London, Wendy B.; Gillies, Stephen D.; Hank, Jacquelyn A.; Voss, Stephan D.; Seeger, Robert C.; Reynolds, C. Patrick; Kimball, Jennifer; Albertini, Mark R.; Wagner, Barrett; Gan, Jacek; Eickhoff, Jens; et al. (Journal of clinical oncology, 2010)
The hu14.18-IL2 fusion protein consists of interleukin-2 molecularly linked to a humanized monoclonal antibody that recognizes the GD2 disialoganglioside expressed on neuroblastoma cells. This phase II study assessed the antitumor activity of hu14.18-IL2 in two strata of patients with recurrent or refractory neuroblastoma. Hu14.18-IL2 was given intravenously (12 mg/m(2)/daily) for 3 days every 4 weeks for patients with disease measurable by standard radiographic criteria (stratum 1) and for patients with disease evaluable only by [(123)I]metaiodobenzylguanidine (MIBG) scintigraphy and/or bone marrow (BM) histology (stratum 2). Response was established by independent radiology review as well as BM histology and immunocytology, and durability was assessed by repeat evaluation after more than 3 weeks. Thirty-nine patients were enrolled (36 evaluable). No responses were seen in stratum 1 (n = 13). Of 23 evaluable patients in stratum 2, five patients (21.7%) responded; all had a complete response (CR) of 9, 13, 20, 30, and 35+ months duration. Grade 3 and 4 nonhematologic toxicities included capillary leak, hypoxia, pain, rash, allergic reaction, elevated transaminases, and hyperbilirubinemia. Two patients required dopamine for hypotension, and one patient required ventilatory support for hypoxia. Most toxicities were reversible within a few days of completing a treatment course and were expected based on phase I results. Patients with disease evaluable only by MIBG and/or BM histology had a 21.7% CR rate to hu14.8-IL2, whereas patients with bulky disease did not respond. Hu14.18-IL2 warrants further testing in children with nonbulky high-risk neuroblastoma.